Tingkat Daya Tahan Jantung Paru Pada Pusat Pendidikan dan Latihan Pelajar Atlet Sepak Bola (PPLP) Pekanbaru Menggunakan Metode Lari 12 Menit - Afandi Ahmad; Miftah Azrin; Firdaus Firdaus (Jurnal Ilmu Kedokteran, 2019)
Cardiorespiratory fitness is defined as the maximum capacity of the heart and lungs to inhale and spread oxygen or abbreviated as VO2 Max. The higher the VO2 max, the higher the body's resistance when exercising, so that an athlete is very important to have a high level of VO2 max. This research was a descriptive study with a sample of all Center for Education and Training soccer athletes measured using the 12-minute run method. Based on the research, the highest age was 15 years with a frequency of 9 (37.5%), with the most practice time was those who practiced for <1 year with a frequency of 15 (62.5%), most of the respondents have normal nutritional status with frequency 17 ( 70.8%), and the highest value of cardiorespiratory fitness (VO2 Max) is sufficient with a frequency of 17 athletes (70.8%).